(untitled) (The Research of Medical Science Review, 2025)
Ten years ago, at the age of 28, an overweight man aged 38 received a diagnosis of Type 1 Diabetes Mellitus (T1DM). His diabetes stayed under control throughout ten years while doctors adjusted his insulin therapy each year without signs of diabetic ketoacidosis developing. Laboratory reanalysis showed high C-peptide markers (5.0 ng/mL) pointed toward well-functioning pancreatic tissues alongside negative autoimmune test results, which led to establishing T2DM as the new diabetes condition. Switching his treatment to the oral antidiabetic medicines metformin and sitagliptan helped him achieve substantial medical benefits through dropping 13 kilograms of weight together with an HbA1c reduction to 6.6%, allowing him to stop taking insulin completely. The correct diagnosis requires C-peptide testing because it distinguishes between Type 1 and Type 2 Diabetes so healthcare providers can select proper treatments that improve patient results.